The time and the space (сhronotope) of Pushkin’s tragedy «Boris Godunov» and actual problems of communication - B.A. Kurkin; O.V. Murashkina (Язык и текст, 2018)
The article is dedicated to analysis of the time- space (chronotope) and genre of A.S. Pushkin’s «Boris Godunov». The Authors analysis the essense of the historical events not only four centuries old but repeat themselves throughout modern times. The Authors a using methods of philosophical hermeneutics and phenomenology in their research.